Maternal and perinatal outcomes of pregnancies complicated by cardiac disease at tertiary level hospital of Uttarakhand - Chaudhari, Priyanka; Gupta, Vineeta; Kumari, Nidhi; Tandon, Archna; Gupta, Nimisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cardiac disease is the most common cause of indirect maternal deaths and most common cause of death overall. It complicates 1% of all maternal deaths. The maternal and neonatal risks associated with pregnancy in women with cardiac disease receiving comprehensive prenatal care have not been well defined. Objective of present study was to evaluate the burden of cardiac diseases in pregnancy in our hospital, their clinical presentation, type of cardiac lesion, associated complications, maternal and fetal outcome. Methods: A retrospective study was conducted in Obstetrics and gynecology department at Shri Guru Ram Rai Institute of medical and health sciences, Dehradun from January- 2013 to December-2015. All patients with cardiac diseases during pregnancy or developed during postpartum period were included in the study. Detailed Demographic profile of patients, mode of delivery, perinatal outcome, associated antenatal, intranatal and postnatal complications were analyzed in detail. Results: There were 37 patients with cardiac disease during pregnancy in our study period. Out of these 32.4% were diagnosed during current pregnancy. Rheumatic heart diseases were seen in 54.05% patients and congenital heart disease seen in 35.1%. out of these 81.1% patients belonged to NYHA class I and II and 18.9% patients in class III & IV. Majority of patients (78.3%) had vaginal delivery. We observed 5.4% maternal mortality and 2.7% of neonatal mortality rate. Conclusions: Pregnancy in women with heart disease is associated with significant cardiac and neonatal complications. Multidisciplinary approach involving cardiologist, obstetrician and neonatologist improves fetomaternal outcome.